Confronting the International Order: Changes in US Foreign Policy from the Perspective of American Power Elites - Mania, Andrzej; Pugacewicz, Tomasz (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
The aim of this article is to present the most important voices on the role of the US in the international order during Donald Trump’s presidency in the debate held in the Foreign Affairs. The authors assume that Foreign Affairs expresses the opinions of the most crucial organisation bringing together the elites of American foreign affairs – the Council on Foreign Relations. The paper proposes a hypothesis according to which there is a difference of opinion due to the adopted theoretical perspective regarding Trump’s role in the destruction of the liberal international order among the American power elites, even though they agree that the ideological conflict between democratic and authoritarian countries around the world is escalating.